AMEAÇAS E VULNERABILIDADES EM SISTEMAS E REDES: UMA ANÁLISE CIENTÍFICA BASEADA EM EVIDÊNCIAS RECENTES - De Lorenzi Ribeiro, Samuel; Langaro Raiser da Cruz, Wesllen Felipe; Wonzoski, Fabiano Oliveira (Seminário de Iniciação Científica e Seminário Integrado de Ensino, Pesquisa e Extensão (SIEPE), 2025)
This study analyzes key contemporary cybersecurity threats, such as malware, phishing, and ransomware, and the critical vulnerabilities that enable them, including weak credentials and outdated software. Through a systematic literature review of articles published between 2023 and 2025, the findings indicate that phishing is responsible for up to 80% of data breaches, while malware accounts for 35% of incidents. As mitigation strategies, the study discusses the implementation of multi-factor authentication (MFA), the use of Artificial Intelligence for proactive threat detection, the adoption of robust security protocols like WPA3 and TLS 1.3, and preparation for emerging risks with quantum-resistant cryptography. It is concluded that building resilient digital ecosystems requires an integrated approach, combining advanced technologies, robust organizational policies, and continuous user education to face an ever-evolving threat landscape.